Treatment of refinery crude oil tank sludge : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Environmental Engineering at Massey University - Guan Hing, Jose B (Massey University, 1999)
The treatment and disposal of oil refinery tank sludge is a critical issue among oil refineries. This is because of the hazardous nature of the sludge due to high levels of oil and heavy metals, which must be removed prior to disposal. This study was carried out to investigate the removal of crude oil and heavy metals to allow the design of an appropriate disposal treatment that could meet the environmental regulations for this type of waste. A typical emulsified crude oil tank sludge, produced from tank cleaning operations was characterised and was shown to contain approximately 41%, 16%, 25%, and 8% of solids (sand), oil, water and volatile materials, respectively. The sludge also contained high level of metals, of which more than 98% resided in the solids fraction. The heavy metals analysed were copper, nickel and zinc with average values of 3,955mg/kg, 443 mg/kg and 13,851 mg/kg of raw sludge, respectively. The crude oil fraction of the sludge was removed by solvent washing with kerosene which resulted in emulsion breakdown. A model which optimises the removal of crude oil was developed and validated against experimental data. The model predictions agreed well with experimental trials using kerosene as the solvent. A 2:1 solvent to sludge ratio is adequate to remove the oil (> 98%) in the sludge after two washing stages. This resulted in oil-free/metal-rich solids. Kerosene washing reduced the volume by 76% and mass by 59%, which allows easier handling and disposal. Heavy metals reduction was achieved by acid washing using 8N nitric acid and a 10:4 mixture of 2.4N hydrochloric and 8N nitric acids. Approximately 99% of the metals were removed using a 10:1 acid to solids ratio, at pH <1 and ambient conditions, making the sludge suitable for land application and meeting the appropriate disposal guidelines for oil and metal levels. The solvent washing process was shown to be industrially feasible for volume and mass reduction of the sludge. However, heavy metal reduction by acid washing requires further optimisation before it can be applied on an industrial scale.
Appendix A-5 held on floppy disk. Please consult print copy in Library.
Keywords: Petroleum refineries; Waste disposal